THE ROLE OF POLITENESS IN INTERCULTURAL COMMUNICATION (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Politeness plays a crucial role in intercultural communication as it serves as a bridge between diverse cultures, fostering mutual respect and understanding. Different cultures have varying norms regarding what is considered polite, and being aware of these differences can prevent misunderstandings and conflict. For instance, in some cultures, directness is valued, while others may interpret it as rudeness. By practicing politeness, individuals can create a welcoming environment that encourages open dialogue and collaboration. Furthermore, politeness can enhance relationships by showing empathy and appreciation for others' viewpoints and traditions. Ultimately, embracing politeness in intercultural interactions not only enriches personal experiences but also promotes global harmony and cooperation